Upaya Meningkatkan Motivasi Belajar Peserta Didik melalui Media Pembelajaran Komik dalam Pembelajaran Pjok - Jojo’ Kholistyono Ngudinur Muhammad; Nanik Indahwati; Demy Ilmiawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research uses the Classroom Action Research (CAR) method with a cyclical approach to increase student learning motivation in Physical Education, Sports and Health (PJOK) subjects. This research was conducted in two cycles, each consisting of planning, implementation, observation and reflection stages. In Cycle I, the average student learning motivation was 44.05%, while in Cycle II it increased significantly to 74.68%, with an increase of 30.63%. This increase shows positive changes in students' interest and enthusiasm for learning. The research results showed that the use of